The effects and influences of South African taxation on the valuation of company shares, business interests and other assets - Shev, Godfrey Leslie (African Cinema Unit, 2021)
This document has been prepared in two parts. The first part deals with some basic aspects of valuations and the major aspects of taxation which should be borne in mind by a valuer. The second part, which commences on page 102, is a compendium of brief comment on tax matters and tax cases which may be of interest to a valuer. The document is based on research carried out in relation to: The Income Tax Act No. 58 of 1962, as amended, inclusive of the 1989 Amending Act; The Sales Tax Act No. 103 of 1978, as amended; and The Estate Duty Act No. 45 of 1955, as amended. Due to subsequent amendments to the legislation certain aspects of taxation dealt with in this document may no longer apply, but there has been comment and expectations in many instances that some of the changes are likely to be reintroduced. I have accordingly included my findings from the research carried out as this could be helpful in the event of a reintroduction of the affected legislation. Since preparing this document, The Sales Tax Act is no longer of force or effect and has been replaced with The Value Added Tax Act of 1991. There are many aspects of this new legislation which also require the consideration and attention of a valuer. I have not dealt with these aspects in detail in this document.